The Impact of Macroeconomic Factors on the Banking Sector’s Profitability in Pakistan - Ayub, Nadia; Bilqees; Shah, Mukamil (Pakistan Journal of Humanities and Social Sciences, 2024)
This research aims to study and analyze the impact of macroeconomic factor on the banking sector’s profitability in Pakistan. Banking sector of Pakistan is the backbone of its economy. The study explains the importance of banking industry of Pakistan and its achievements and evolvement throughout the years. The objective of the study is to examine the macroeconomic factors’ influence on the banking sector in Pakistan and to investigate that whether the profitability is only determined by the bank-specific internal factors or if it is also influenced by macroeconomic shocks and factors of the economy. The study is quantitative and secondary data is employed in order to conduct this paper. The sample size is financial data of scheduled banks in Pakistan from the year 2000 to2022, which is converted in quarter data and 84 observations have been incorporated in the study. “Returns on Assets” (ROA) is selected as dependent variable of this study since it measures profitability of banks. Whereas “Foreign Direct Investment” (FDI), “Exchange rate” (LER), “Inflation” (INF), “GDP growth” (GROWTH), “Liquidity” (LLIQ), “Total Deposits” (LT_DEP) and “Credit’s ratio” (CREDIT) of the banks are selected as independent variables. The data for bank specific variables is collected from the websites of “State Bank of Pakistan” (SBP) and “Federal Reserves of Economic Data” (FRED) while the data for macroeconomic variables is derived from the database of “World Bank” and “Macrotrends”. For empirical analysis, we have applied “Vector Autoregression” (VAR) model, followed by “Multivariate Granger Causality test”, “Impulse Response Function” (IRF) and “Forecast Error Variance Decomposition” (FEVD). The main findings of study reveals that the profitability of Banking sector in Pakistan is more influenced by its own internal factors rather than the external / macroeconomic factors. Amongst macroeconomic variables, “Foreign Direct Investment” (FDI) and “Inflation” (INF) are found to have the significant impact, while “Exchange rate” (LER) and “GDP growth rate” (GROWTH) are found to have insignificant impact on banks’ “Return on Assets” (ROA). All the internal factors of our study i.e. “Liquidity” (LLIQ), “Deposits” (LT_DEP) and “Credit ratio” (CREDIT) are found to have significant impact on profitability, which is measured through “Return on Assets” (ROA). In short, the profitability of banking sector in Pakistan is mainly influenced by bank-specific internal factors of the industry. The macroeconomic factors are only 50 percent % affective on the banks’ performance.